2022
DOI: 10.1097/gox.0000000000004300
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Gap: Training Experiences and Career Outcomes for Underrepresented Minorities in Plastic Surgery

Abstract: Background: The present study assesses training characteristics, scholastic achievements, and traditional career accomplishments of ethnically underrepresented in medicine (UIM) plastic and reconstructive surgery (PRS) faculty relative to non-UIM PRS faculty. Method: A cross-sectional analysis of core PRS faculty appointed to accredited United States residency training programs (n = 99) was performed. Results: Of the 949 US PRS faculty, a total of 51 (5.4%) were identified as UIM. Compared with non-UIM faculty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…35,36 To ensure a more diverse group of plastic surgeons in the future, we must provide those who are underrepresented with equal opportunities to attain a residency and excel academically in plastic surgery. 10,13 One of the greatest barriers to initial entrance into plastic surgery and future promotion for underrepresented groups is poor confidence, stemming from a lack of visual confirmation from those with similar demographic backgrounds in positions of leadership or prestige. 1,24 Invited speakers at national conferences embody an opportunity to provide this visual representation of diversity and equal opportunity within the field.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…35,36 To ensure a more diverse group of plastic surgeons in the future, we must provide those who are underrepresented with equal opportunities to attain a residency and excel academically in plastic surgery. 10,13 One of the greatest barriers to initial entrance into plastic surgery and future promotion for underrepresented groups is poor confidence, stemming from a lack of visual confirmation from those with similar demographic backgrounds in positions of leadership or prestige. 1,24 Invited speakers at national conferences embody an opportunity to provide this visual representation of diversity and equal opportunity within the field.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,8,10 African Americans and Hispanic or Latino Americans each make up less than 5% of plastic surgery residents and faculty in the United States, with no significant increases in representation over the last decade. 3,10,11 Diversifying the field of academic plastic surgery can provide immeasurable benefits to a healthcare system with long-standing gender and racial disparities. 2,3,[12][13][14][15][16] More diverse teams of physicians demonstrate better patient outcomes and superior patient-rated clinical care, whereas physicians of a non-White ethnicity are more likely to address existing health disparities and attend to the underserved community.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Chawla et al 60 reported that citations and h-indices of White and non-White academic plastic surgeons were comparable. Diatta et al 79 found that underrepresented academic faculty have fewer years in practice than their nonunderrepresented counterparts (8 vs 12 years), reflecting a significant increase in their representation in recent years. Smith et al 22 reported that non-White plastic surgeons were less likely than Whites to hold a full professor position.…”
Section: Continued Next Pagementioning
confidence: 99%